IMPLEMENTATION OF SRI (SYSTEM OF RICE INTENSIFICATION) FOR INCREASING PADDY PRODUCTION AND SMALLHOLDER SELF SUFFICIENCY - Luh Putu Suciati; Bambang Juanda (UPT Penerbitan Universitas Jember, 2012)
This study provides empirical evidence by analyzing SRI adoption in the small farm sector in Citarum river basin, West Java, upstream region represented by Cianjur while the downstream region is represented by Karawang. Rice production will increase by application of the SRI method although there are additional costs related to farm labor. At the same price of rice, in the short run, increasing in production will increase farmers'income and in the long run, maintain the ecological sustainability of land. Increased production and improved soil conditions will ensure self-sufficiency of small farmers. The root problem and key issues in the implementation of SRI method at Cianjur related with lack of incentives for farmers to implement new methods. As in Karawang, the root cause of application SRI method related with no guarantee of market and government policyrelated market aspects.